Diagnosis and management of male urinary tract infections: a need for new guidelines. Study from a French general practice electronic database. (19th December 2020) - Soudais, Benjamin; Lacroix-Hugues, Virginie; Meunier, François; Gillibert, André; Darmon, David; Schuers, Matthieu
Abstract: Background: The definition and the treatment of male urinary tract infections (UTIs) are imprecise. This study aims to determine the frequency of male UTIs in consultations of general practice, the diagnostic approach and the prescribed treatments. Methods: We extracted the consultations of male patients, aged 18 years or more, during the period 2012–17 with the International Classification of Primary Care, version 2 codes for UTIs or associated symptoms from PRIMEGE/MEDISEPT databases of primary care. For eligible consultations in which all symptoms or codes were consistent with male UTIs, we identified patient history, prescribed treatments, antibiotic duration, clinical conditions, additional examinations and bacteriological results of urine culture. Results: Our study included 610 consultations with 396 male patients (mean age 62.5 years). Male UTIs accounted for 0.097% of visits and 1.44 visits per physician per year. The UTIs most commonly identified were: undifferentiated (52%), prostatitis (36%), cystitis (8.5%) and pyelonephritis (3.5%). Fever was recorded in 14% of consultations. Urine dipstick test was done in 1.8% of consultations. Urine culture was positive for Escherichia coli in 50.4% of bacteriological tests. Fluoroquinolones were the most prescribed antibiotics (64.9%), followed by beta-lactams (17.4%), trimethoprim-sulfamethoxazole (11.9%) and nitrofurantoin (2.6%). Conclusions: Male UTIs are rare in general practice and have different presentations. The definition of male UTIs needs to be specified by prospective studies. Diagnostic evidence of male cystitis may reduce the duration of antibiotic therapy and spare critical antibiotics. Lay Summary: The definition and the treatment of male urinary tract infections (UTIs) are imprecise. We aimed to determine the frequency of male UTIs, the diagnostic approach and the prescribed treatments in French electronic health records of general practice. Our study included 610 consultations with 396 male patients with UTIs. In most cases, the organic site of the UTI was not determined. Prostatitis, cystitis and pyelonephritis were diagnosed to a lesser degree. Most patients did not have fever. Half of urine cultures were positive for Escherichia coli, a bacterium from the gastrointestinal tract. Antibiotics were the treatment of choice for male UTIs. In our study, fluoroquinolones (FQs) were the most prescribed antibiotics, then beta-lactams, trimethoprim-sulfamethoxazole and nitrofurantoin. All infections were treated in the same way. Male UTIs are rare in general practice and have different presentations. The resistance of bacteria to FQs is increasing. General practitioners should prescribe antibiotics carefully to avoid failure in the event of recurrent infections. Treating cystitis, prostatitis and pyelonephritis differently may reduce the duration of antibiotic therapy and spare critical antibiotics.